Prevalence of 12-Month Alcohol Use, High-Risk Drinking, and DSM-IV Alcohol Use Disorder in the United States, 2001-2002 to 2012-2013: Results From the National Epidemiologic Survey on Alcohol and Related Conditions - Grant, Bridget F; Chou, S Patricia; Saha, Tulshi D; Pickering, Roger P; Kerridge, Bradley T; Ruan, W June; Huang, Boji; Jung, Jeesun; Zhang, Haitao; Fan, Amy; Hasin, Deborah S (JAMA psychiatry (Chicago, Ill.), 2017)
Lack of current and comprehensive trend data derived from a uniform, reliable, and valid source on alcohol use, high-risk drinking, and DSM-IV alcohol use disorder (AUD) represents a major gap in public health information. To present nationally representative data on changes in the prevalences of 12-month alcohol use, 12-month high-risk drinking, 12-month DSM-IV AUD, 12-month DSM-IV AUD among 12-month alcohol users, and 12-month DSM-IV AUD among 12-month high-risk drinkers between 2001-2002 and 2012-2013. The study data were derived from face-to-face interviews conducted in 2 nationally representative surveys of US adults: the National Epidemiologic Survey on Alcohol and Related Conditions, with data collected from April 2001 to June 2002, and the National Epidemiologic Survey on Alcohol and Related Conditions III, with data collected from April 2012 to June 2013. Data were analyzed in November and December 2016. Twelve-month alcohol use, high-risk drinking, and DSM-IV AUD. The study sample included 43 093 participants in the National Epidemiologic Survey on Alcohol and Related Conditions and 36 309 participants in the National Epidemiologic Survey on Alcohol and Related Conditions III. Between 2001-2002 and 2012-2013, 12-month alcohol use, high-risk drinking, and DSM-IV AUD increased by 11.2%, 29.9%, and 49.4%, respectively, with alcohol use increasing from 65.4% (95% CI, 64.3%-66.6%) to 72.7% (95% CI, 71.4%-73.9%), high-risk drinking increasing from 9.7% (95% CI, 9.3%-10.2%) to 12.6% (95% CI, 12.0%-13.2%), and DSM-IV AUD increasing from 8.5% (95% CI, 8.0%-8.9%) to 12.7% (95% CI, 12.1%-13.3%). With few exceptions, increases in alcohol use, high-risk drinking, and DSM-IV AUD between 2001-2002 and 2012-2013 were also statistically significant across sociodemographic subgroups. Increases in all of these outcomes were greatest among women, older adults, racial/ethnic minorities, and individuals with lower educational level and family income. Increases were also seen for the total sample and most sociodemographic subgroups for the prevalences of 12-month DSM-IV AUD among 12-month alcohol users from 12.9% (95% CI, 12.3%-17.5%) to 17.5% (95% CI, 16.7%-18.3%) and 12-month DSM-IV AUD among 12-month high-risk drinkers from 46.5% (95% CI, 44.3%-48.7%) to 54.5% (95% CI, 52.7%-56.4%). Increases in alcohol use, high-risk drinking, and DSM-IV AUD in the US population and among subgroups, especially women, older adults, racial/ethnic minorities, and the socioeconomically disadvantaged, constitute a public health crisis. Taken together, these findings portend increases in many chronic comorbidities in which alcohol use has a substantial role.